Ectopic Thyroid Incidence with its Hormonal Assessment (TAJ: Journal of Teachers Association, 2010)
Ectopic thyroid tissue has been found from the tongue to the diaphragm. Ninety percent of the reported cases of ectopic thyroid are found in the base of the tongue Total numbers of 1895 cases were included in this study. Patients were sending to CNMU-Rajshahi during the period of January’2006 to June 2009 for thyroid scanning as well as evaluation of thyroid functional status. Radio-active iodine drink / Tc99m pertachnatate I/V were given to the patients for thyroid scan. Biochemical analyses were done for the ectopic thyroid patient. Among them 17.85% patients had hypothyroidism. Only 1.5%(28) patients have diagnosed as ectopic thyroid majority of the cases had lingual thyroid (10), sub-lingual thyroid in 06, over cricoid cartilage in 05 and others were seen in sub-mandibular and sub-mental region.. This study aims to find out the incidence of ectopic thyroid tissue and its functional status.TAJ 2010; 23(1): 18-21